2011
DOI: 10.1111/j.1365-2788.2011.01512.x
|View full text |Cite
|
Sign up to set email alerts
|

More academics in regular schools? The effect of regular versus special school placement on academic skills in Dutch primary school students with Down syndrome

Abstract: Regularly placed children with Down syndrome learn more academics. However, this is not a straight consequence of inclusive placement and age alone, but is also determined by factors such as cognitive functioning, non-academic skills, parental educational level and the extent to which parents worked at home on academics. Nevertheless, it could be proven that the more advanced academic skills of the regularly placed children are not only due to selective placement. The positive effect of regular school on acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 14 publications
3
29
0
1
Order By: Relevance
“…2012a; de Graaf et al . ), still many parents of children with Down syndrome or similar intellectual disabilities (ID) have to invest extraordinary levels of time, energy and resources in their struggle to get their children into mainstream school and to support their educational progress, once there (Cuckle ; van Hove ; Lorenz ; Ghesquière et al . ; Kenny et al .…”
Section: Introductionmentioning
confidence: 99%
“…2012a; de Graaf et al . ), still many parents of children with Down syndrome or similar intellectual disabilities (ID) have to invest extraordinary levels of time, energy and resources in their struggle to get their children into mainstream school and to support their educational progress, once there (Cuckle ; van Hove ; Lorenz ; Ghesquière et al . ; Kenny et al .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, in the Netherlands, around 68% of the parents of young children with Down syndrome make use of an early intervention program, and around 60% of these parents receive professional support in working with such a program (de Graaf, de Graaf, & Borstlap, 2011). With respect to inclusion in education, in the late 1980s and early 1990s, the numbers of children with Down syndrome starting in a regular school were rising fast (de Graaf, van Hove, & Haveman, 2014). Since 1995, an estimated 56% of all children with Down syndrome in the Netherlands start their school career in regular education (de Graaf et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to inclusion in education, in the late 1980s and early 1990s, the numbers of children with Down syndrome starting in a regular school were rising fast (de Graaf, van Hove, & Haveman, 2014). Since 1995, an estimated 56% of all children with Down syndrome in the Netherlands start their school career in regular education (de Graaf et al, 2014). Further, as special classrooms inside regular schools are very rare, education almost always involves placement in a regular classroom with a certain amount of extra support (de Graaf & van Hove, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Dutch study showed that children with DS in mainstream education learn more academics, most pronounced for reading skills. However these advantages were also determined by other factors, such as parental educational level [5].…”
Section: Introductionmentioning
confidence: 99%